Pelatihan Pengolahan Hasil Perikanan Bagi Perempuan Pesisir Di Desa Padak Guar - As'urin, B.; Sulastri, Sulastri (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
One of the problems in Padak Guar Village is the lack of access to information and knowledge, which has an impact on the abilities (skills) of coastal women. The aim of this community service activity is to increase the knowledge and skills of coastal women, especially in processing fishery products; demonstrate safe and healthy fishery product processing techniques; Provide skills and knowledge of production costs and selling prices for marketing. The method of implementing this service uses a demonstration method, namely explaining how to process fishery products into fish nuggets; The practical method is to directly practice how to make fish nuggets; The discussion method is carried out after completing the practicum with the aim of knowing the participants' responses. The results of the activity show that increasing the knowledge and skills of coastal women in handling fish until it becomes a product; Increasing coastal women's awareness of the importance of increasing and developing coastal women's skills in diversifying fishery products; The birth of a desire that becomes a necessity for coastal women to become productive women; Increased knowledge of coastal women in determining the amount of capital and determining the selling price of products. From this activity it can be concluded that coastal women have high enthusiasm, shown by their enthusiasm and participation during the activity. And the knowledge and insight of coastal women is starting to open up according to their perspective that women must be productive women, not consumptive women.